Noninvasive Neurological Monitoring in Extracorporeal Membrane Oxygenation. Issue 4 (April 2020) - Cho, Sung-Min; Ziai, Wendy; Mayasi, Yunis; Gusdon, Aaron M.; Creed, Jennifer; Sharrock, Matthew; Stephens, Robert Scott; Choi, Chun Woo; Ritzl, Eva K.; Suarez, Jose; Whitman, Glenn; Geocadin, Romergryko G.
Abstract : Optimal neurologic monitoring methods have not been characterized for patients on extracorporeal membrane oxygenation (ECMO). We assessed the feasibility of noninvasive multimodal neuromonitoring (NMN) to prognosticate outcome. In this prospective observational study, neurologic examinations, transcranial Doppler (TCD), electroencephalography (EEG), and somatosensory evoked potentials (SSEPs) were performed at prespecified intervals. Outcome at discharge was defined as favorable when modified Rankin Scale (mRS) 0–3; unfavorable when mRS >3. Of 20 patients (median age 60 years), 17 had TCDs, 13 had EEGs, and seven had SSEPs. With NMN, 17 (85%) were found to have neurologic complications. Fourteen (70%) had unfavorable outcomes. The unfavorable outcome was associated with absent EEG reactivity, coma, central cannulation, higher transfusion requirement, and higher Acute Physiology and Chronic Health Evaluation II and Sepsis-related Organ Failure Assessment scores. Seven patients had both SSEPs and EEGs and exhibited intact N20 responses despite poor outcomes. Four of these seven showed absent EEG reactivity despite intact N20. Eighteen thromboembolic events were observed, 14 of which had positive microembolic signals (MESs) in TCD. All 10 patients with arterial-sided thrombotic events had positive MES. NMN caused no adverse effects. NMN during ECMO is feasible and found high neurologic complication rate. EEG and TCD showed potential for prognostication of neurologic outcome. Abstract : Supplemental Digital Content is available in the text.